Treatment with (R)-α-methylhistamine or IL4 stimulates mucin production and decreases Helicobacter pylori density in the murine stomach - Santos, Licínia; Sharba, Sinan; Benktander, John; Ojaimi Loibman, Stefany; Quintana-Hayashi, Macarena P.; Erhardsson, Mattias; Lindén, Sara K. (University of Gothenburg, 2025)
The histology data show the sum scores for each group used to calculate the results in percentages normalized to non-infected vehicle-treated or H. pylori-infected vehicle-treated mice allowing for pooling results from different experiments into the same graph.
The antibody levels determined by ELISA are presented in absorbance 450nm.
The cell growth/viability was measured as the reducing potential of viable cell data presented in luminescence.
The expression of virulence factor assessed by RT-PCR is expressed in fold-change.

Histologiska data visar summapoängen för varje grupp som användes för att beräkna resultaten i procentandelar normaliserade till icke-infekterade vehikelbehandlade eller H. pylori-infekterade vehikelbehandlade möss, vilket möjliggör sammanslagning av resultat från olika experiment i samma graf.
Antikroppsnivåerna bestämda med ELISA presenteras i absorbans 450 nm.
Celltillväxten/viabiliteten mättes som den reducerande potentialen för viabla celldata presenterade i luminescens.
Uttrycket av virulensfaktor bedömd med RT-PCR uttrycks i veck-förändring.
Treatment with (R)-α-methylhistamine or IL4 stimulates mucin production and decreases Helicobacter pylori density in the murine stomach
Treatment with RαMH or IL4 stimulates mucin production and decreases Helicobacter pylori density in the murine stomach
Keywords: Mucins; Muciner; Mucus; Slem; Stomach; Magsäck; mouse; mus; H. pylori; H. pylori; HEALTH; HÄLSA; Medication and treatment; Medicinering och behandlingar; Biological Sciences; Biologi; Microbiology; Mikrobiologi; Molecular Biology; Molekylärbiologi